2012
DOI: 10.4172/1948-5948.s8-001
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications for Controlled and Optimized Cell Immobilization by Adsorption: Applications in Fibrous Bed Bioreactors Containing Recombinant Cells

Abstract: The effects of surface properties of S. cerevisiae strains 468/pGAC9 and 468 on adhesion to polyethylenimine (PEI) and/glutaraldehyde (GA) pretreated cotton (CT), polyester (PE), polyester + cotton (PECT), nylon (NL), polyurethane foam (PUF), and cellulose re-enforced polyurethane (CPU) fibers were investigated. Process parameters (circulation velocity, pH, ionic strength, media composition and surfactants) were also examined. 80, 90, and 35% of the cells were adsorbed onto unmodified CT, PUF and PE, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The highest efficiency in the degradation of ophthalate by cells Bacillus-spp. immobilized in polyurethane foam, in relation to alginate was reported by Donlan (2002) and Kilonzo and Bergougnou (2012). Patil et al (2006).…”
Section: Adsorptionmentioning
confidence: 88%
See 2 more Smart Citations
“…The highest efficiency in the degradation of ophthalate by cells Bacillus-spp. immobilized in polyurethane foam, in relation to alginate was reported by Donlan (2002) and Kilonzo and Bergougnou (2012). Patil et al (2006).…”
Section: Adsorptionmentioning
confidence: 88%
“…Different from the inherent problems associated with cell entrapment, cell immobilization through adsorption provides a direct contact between nutrients and the immobilized cells thus, eliminating such concerns (Braschler et al, 2005). This cell immobilization technique involves the transport of the cells from the bulk phase to the surface of support (porous and inert support materials), followed by the adhesion of cells, and subsequent colonization of the support surface (Kilonzo and Bergougnou, 2012).…”
Section: Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors [34] reported an increase of cell loading with increasing ionic strength and others [35] reported no net apparent effect of ionic strength on the cell adsorption. However, in viable cell immobilization, it is expected that under the experimental conditions, a high ionic strength might destabilize immobilized cells and prevents the interaction between cells and supports surfaces, and thereby reduces the cell adhesion [36].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Phase diagrams are usually constructed based on the experimental results in order to understand the performance of the magnetic particles under the mutual effect of the magnetic field used for stabilization or separation purposes and the liquid flow in the bed [36]. These experiments were conducted in "magnetizing first" mode in which the magnetic particles were poured in the water filled column to form a packed bed of certain height.…”
Section: Hydrodynamic Behavior Of the Magnetic Particles In Msfbsmentioning
confidence: 99%